The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1159/000139239
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ATP-Sensitive Potassium Channel-Blocking Activity of ZENECA ZM 181,037, a Eukalemic Diuretic

Abstract: ZENECA ZM181,037 is a novel eukalemic diuretic from a series of 1,1-diarylcarbin-1-01-2 amines. In contrast to the standard diuretic hydrochlorothiazide, the blood pressure-lowering effect was not observed with ZENECA ZM 181,037 in spontaneously hypertensive rats. ZENECA ZM 181,037 demonstrated a K+ channel-blocker profile. In the isolated rat aorta stimulated with 20 mmol/l KC1, both the d- and l-enantiomer of ZENECA ZM 181,037 antagonized the relaxation of cromakalim with mean pKB value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…The sulphonylurea tolbutamide was observed to have similar glucose-lowering and insulin-secreting effects to BTS 67 582, though at comparable doses the effects of BTS 67 582 were slightly slower in onset and were shorter lived. The activity of tolbutamide in this experiment was similar to that previously observed in dogs where an intravenous dose of 25 mg/kg (92.4 µmol/kg) tolbutamide caused an approximate 50% reduction in plasma glucose 2 h after administration [Kau et al, 1994]. The dose causing a 25% reduction of plasma glucose values was similar for both BTS 67 582 (24.7 µmol/kg) and tolbutamide (22.7 [Geisen, 1988].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The sulphonylurea tolbutamide was observed to have similar glucose-lowering and insulin-secreting effects to BTS 67 582, though at comparable doses the effects of BTS 67 582 were slightly slower in onset and were shorter lived. The activity of tolbutamide in this experiment was similar to that previously observed in dogs where an intravenous dose of 25 mg/kg (92.4 µmol/kg) tolbutamide caused an approximate 50% reduction in plasma glucose 2 h after administration [Kau et al, 1994]. The dose causing a 25% reduction of plasma glucose values was similar for both BTS 67 582 (24.7 µmol/kg) and tolbutamide (22.7 [Geisen, 1988].…”
Section: Discussionsupporting
confidence: 87%
“…It is possible, therefore, that BTS 67 582 exerts it diuretic activity via inhibition of renal tubular KATP channels. The diuretics ZM181,037 [Kau et al, 1994] and U-37883A [Perricone et al, 1994;Humphrey et al, 1995;Humphrey, 1995] have been reported to cause eukalemic diuresis in dogs broadly similar to that observed with BTS 67 582. Interestingly, ZM181,037 and U-37883A [Wang et al, 1995] inhibit renal tubular KATP channel activity and possess functional antagonism of KATP channels in vascular tissue, but are devoid of glucose-lowering activity.…”
Section: Discussionmentioning
confidence: 82%
“…This unusal profile is similar to that of tubular KAT p channel blockers; however, direct evidence for such a mechanism of action is lacking. In a subsequent study it was shown that micromolar concentrations of the compound inhibited cromakalim-induced vasorelaxation and a6Rb+ efflux, demonstrating that the compound is a potent blocker of vascular Km-p channels (Kau et al 1994). At concentrations which produce strong renal effects (Kau et al 1991), no decrease in blood glucose was observed, excluding an effect on pancreatic KATP channels (Kau et al 1994).…”
Section: Upjohn U-37883amentioning
confidence: 98%
“…In a subsequent study it was shown that micromolar concentrations of the compound inhibited cromakalim-induced vasorelaxation and a6Rb+ efflux, demonstrating that the compound is a potent blocker of vascular Km-p channels (Kau et al 1994). At concentrations which produce strong renal effects (Kau et al 1991), no decrease in blood glucose was observed, excluding an effect on pancreatic KATP channels (Kau et al 1994). The ability of the compound to protect against ouabain-induced arrhythmias (Kau et al 1991) suggests that the compound interferes with additional targets as well.…”
Section: Upjohn U-37883amentioning
confidence: 99%
“…1) as a novel eukalemic diuretic with thiazide-like efficacy that does not affect urinary K + excretion or plasma K + levels. Despite its diuretic action, ZM181,037 failed to reduce blood pressure in hypertensive rats (62). Subsequent vascular studies demonstrated that like PNU-37883A, this agent also blocks cromakalim in 20 mM KCl-contracted rat aorta with a pK b of 6.5, and similar K-ATP opener antagonism was seen in guinea pig portal vein and detrusor muscle.…”
Section: Zm181037mentioning
confidence: 96%